Sustainable Cement Development Using Palm Oil Boiler Ash: Mechanical and Microstructural Evaluation - Suraedi, Daral; Sjah, Jessica; Handika, Nuraziz; Jonbi; Ashari, Ahmad (Science and Technology Indonesia, 2025)
The cement industry significantly contributes to CO2 emissions, releasing approximately 1 ton of CO2 for every ton of cement produced, which accounts for up to 40% of total global industrial emissions. This study aims to mitigate these emissions by utilizing Palm Oil Boiler Ash (POBA) as a clinker substitute, creating POBA Cement with substitution levels ranging from 10% to 30%. The POBA was sourced from the Cikasungka Palm Oil Plantation in Bogor, Indonesia and underwent analysis using X Ray Fluorescence (XRF) andScanningElectron Microscopy (SEM) to assess its chemical properties and microstructure. The findings revealed a decrease in compressive strength with increased POBA substitution levels; however, it maintained a pozzolanic effect that supported the crystallization process, albeit with a longer setting time compared to Ordinary Portland Cement (OPC). Notably, the addition of 1% nano-silica was found to enhance compressive strength more effectively than 3%. This research underscores the potential of POBA as an environmentally friendly clinker substitute for sustainable cement production.